Learning History, Perception, and Attitude towards Kartini Figure in SMA N 2 Rembang - Bakhri, Mohammad Syaiful; Utomo, Cahyo Budi; Bain, Bain (Universitas Negeri Semarang, 2021)
The study aimed to determine the effect of Kartini sub-material history learning and student perceptions of student attitudes towards Kartini figures in class XI of SMA 2 Rembang in 2018. This type of research is ex post facto research. The results showed that historical learning and student perceptions affected students' attitudes towards Kartini. This is evidenced by the F Test, which obtained an F count greater than Ftable 5.522> 1.653; in the partial test (t test) for the Kartini sub miniate history learning variable (X1) obtained a t count smaller than t table 0.778 1.653, so H2 is accepted. Simultaneously, history learning and student perceptions affect student attitudes towards Kartini's figure of 4.6%. Partially, the influence of historical learning on student attitudes toward the Kartini figure was 0.32%, and the influence of students' perceptions of student attitudes towards the Kartini figure was 4.6%.